Effects of hydraulic retention time on biohythane production via single-stage anaerobic fermentation in a two-compartment bioreactor. (November 2019) - Vo, Tan-Phat; Lay, Chyi-How; Lin, Chiu-Yue
Graphical abstract: Highlights: Anaerobic two-compartment biohythane reactor was developed. HRTs affected substrate removal efficiency and biohythane production. HRT 2 d gave peak H2 and CH4 production rates of 714 and 254 mL/L-d, respectively. C. sensu stricto 2 and Methanosaeta dominated in H2 and CH4 layers, respectively. Abstract: Hythane has been well known as a mixture of hydrogen and methane gases but their production is mostly in a different way. The present study dealt with the potential biohythane production in a two-compartment (lower, hydrogenesis; upper, methanogenesis) reactor via a single-stage anaerobic fermentation at mesophilic temperature. The effect of hydraulic retention time (HRT) was tested at 10–2 d using food waste substrate. HRT 2 d resulted in (1) maximum removal efficiencies for COD, carbohydrate, lipid and protein contents with values of 58.5, 58.4, 62.6 and 79.1%, respectively; (2) peak hydrogen and methane production rates of 714 and 254 mL/L-d, respectively; and (3) biogas contents of hydrogen 8.6% and methane 48.0% in the produced gas. At this HRT, Clostridium sensu stricto 2 and Methanosaeta were dominant species in H2 and CH4 compartments, respectively. The novelty of this work is creating a novel two-compartment reactor for single-stage anaerobic biohythane fermentation.